2018
DOI: 10.18632/oncotarget.26107
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as oncotarget: a comparison between the tetracycline analogs doxycycline and COL-3

Abstract: Tetracyclines have anticancer properties in addition to their well-known antibacterial properties. It has been proposed that tetracyclines slow metastasis and angiogenesis through inhibition of matrix metalloproteinases. However, we believe that the anticancer effect of tetracyclines is due to their inhibition of mitochondrial protein synthesis, resulting in a decrease of the mitochondrial energy generating capacity. Several groups have developed analogs that are void of antibacterial action. An example is COL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Several groups have reported that doxycycline induces apoptosis in other cancer cell lines at higher doxycycline concentrations than used here 24,49,50,55 . We found that doxycycline treatment did not induce caspase 9, 8 or 3/7 activity in A549 cells, supporting our earlier observations that doxycycline does not cause activation of procaspase 3 52 . However, doxycycline and gemcitabine co-treatment resulted in a strong induction of caspase 9 and 3/7 activity when compared to gemcitabine alone.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…Several groups have reported that doxycycline induces apoptosis in other cancer cell lines at higher doxycycline concentrations than used here 24,49,50,55 . We found that doxycycline treatment did not induce caspase 9, 8 or 3/7 activity in A549 cells, supporting our earlier observations that doxycycline does not cause activation of procaspase 3 52 . However, doxycycline and gemcitabine co-treatment resulted in a strong induction of caspase 9 and 3/7 activity when compared to gemcitabine alone.…”
supporting
confidence: 91%
“…The western blots showed that the doxycycline-induced decrease of MTCO1 and MTCO2 in A549 cells flattens after 3 days of treatment. Earlier, we showed that a proliferation slowdown of A549 cells occurs after 3 days of doxycycline treatment 52 . Apparently, at this point, the mitochondrial energy generating capacity is too low to maintain normal cell proliferation.…”
mentioning
confidence: 84%
See 3 more Smart Citations